(untitled) (Applied Biological Research, 2023)
The presentstudy focused on the screening of therapeutically valuable secondary metabolites and FTIR analysis of sequential leaf and bark extracts and direct powder of Erinocarpus nimmonii Grah. ex Dalz., an endemic medicinal species ndary metabolites were screened by using standard methods.FTIR spectral profiling of all extracts and powder was done, and matched with a set opeak values specific for each secondary metabolite. The phytochemical screening showed the presence ofsaponin, terpenoids, steroids, triterpenoids, gum and mucilage, but not alkaloids. The FTIprofile showed coinciding peak values specific for all the biomolecules tested, except alkaloids. Further, the presence of bidesmosidic triterpenoid saponin in leaf extract, alkyne in bark extract, and absence of cyanide peak were disclosed. This simple, affordable, and novel approach of secondary metabolite validation directs further advancement towards fractionation, while the use of direct powder still expedites the procedure by skipping the laborious extraction process. It enables the revelation of therapeutic biomolecules capped on green metallic nanoparticles. To be concise, it is straightforward way to bridge the gap between the spectral profile of plants with the actual secondary metabolites they own.